Renal Tubular Cells from Hibernating Squirrels are Protected against Cisplatin Induced Apoptosis. (4th August 2020) - Jain, Swati; Jani, Alkesh
Abstract : Hibernating 13-lined ground squirrels are characterized by tolerance of severe hypothermia and hypoperfusion during torpor, followed by periodic warm reperfusion during IBA, conditions which are lethal to nonhibernating mammals. The aim of the present study was to determine whether protection from apoptosis was specific to torpor arousal cycles during hibernation or will also apply to cisplatin treatment on squirrel renal tubular cells (RTECs) that were procured during hibernation. Squirrel and mouse RTECs were treated with cisplatin, a potent inducer of RTEC apoptosis. Squirrel RTECs subjected to cisplatin had significantly less apoptosis, no cleaved caspase-3, and increased XIAP, pAkt, and pBAD versus mouse RTECs. To determine whether XIAP and Akt1 are necessary for RTEC protection against cisplatin induced apoptotic cell death, gene expression of Akt1 or XIAP was silenced in squirrel RTECs. Squirrel RTECs deficient in Akt1 and XIAP had increased apoptosis and cleaved caspase-3 when treated with cisplatin. Our results thus demonstrates that 13-lined ground squirrel RTECs possess intrinsic intracellular mechanisms by which they protect themselves from apoptotic cell death. Cisplatin induced acute kidney injury (AKI) may be avoided in cancer patients by employing mechanisms used by squirrel RTECs to protect against cisplatin induced tubular cell apoptosis.